Retroperitoneal Sarcomas - Herman, Krzysztof; Kusy, Tomasz (Contemporary Oncology/Współczesna Onkologia, 1999)
Retroperitoneal sarcomas (RS) are rare malignant neoplasms (1-2 cases per million per year). Only a few centres could attain some experience in this field. Usually large size of tumours are due to the slow growth and not common symptoms. Different histologic types, grades and uncommon incidence make any comparison difficult. Radical excision including adjacent organs called „en-block” resection is the treatment of choice. Complete tumour excision remains a challenge even for an experienced surgeon. In the published series resectability ranges from 38% to 100% with radicality rate from 8% to 95%. Local recurrences are very common (33%–86%), with rare distant metastases (max. 33%), so local failure is usually a cause of death. It is well known that histological grading and completeness of surgery influence survival chances. Five year survival rates after radical excision ranged from 62%–92% in well differentiated tumours compared with 16%–48% in nondifferentiated sarcomas. There are no evident data that adjuvant or neoadjuvant treatment does influence prognosis. It seems, that only international multicenter studies might help in evaluating treatment and in application of innovative multimodality therapies to these neoplasms.